There is no Conflict between the Qur’ān and the Hadith: Analysis of Orientalist John Burton’s Objections - Muhammad Khubaib; Sajid U Rahman (jihat-ul-islam, 2023)
John Burton is an Orientalist. He has written a book regarding the Holy Qur’ān named “The Collection of the Qur’ān”. In the second chapter of his book he has objected on the Qur’ān due to Disagreements among the four Mad’āhib of Islām. He claims that difference in the rulings of four Mad’āhib of Islām means that the rulings of the Qur’ān are different. He also writes that there is conflict between the Qur’ān and the Hadith. In this article John Burton’s objections on the Qur’ān regarding Islāmic Rulings (Ahkām) have critically been analyzed. In this regard, the meanings of Fiqh and Usūl-e-Fiqh have been explained and it has been clarified that difference in fiqh of Mad’āhib-e-Arba’ is not due to the conflict in the Qur’ān. The sayings of the founders of the four Mad’āhib; Imām Abu Hanīfa, Imām Malik bin Anas, Imām Shafī and Imām Ahmad bin Hanbal to follow the Qur’an and Hadīth, have also been quoted. Then Burton’s view that there is conflict between the Qur’ān and the Hadīth, has also been negated in the light of the Qur’ān and the Hadīth.